Evaluation of the Immunological and Hematological parameters of Systemic Lupus Erythematosus in Iraqi Women - Mohsen, Rana; Abdulazeez , Riyadh Ali ‎; Haneen Z. Al-Taee; Wafaa Hussien Habeeb; Anmar Kamil (University of Thi-Qar Journal of Science, 2024)
Systemic lupus erythematosus is an autoimmune disease involving several systems, mainly affects young adult women, and causes a significant deterioration in quality of life. Different environmental aspects are known to facilitate the development of lupus in predisposed individuals. Hemoglobin concentration (HB), granulocyte level, hemoglobin level, saturation (ESR), and platelets (PLT) were among the clinical blood indicators that were found to be associated with the beginning of SLE in adults and teenagers. Blood PLT levels in both SLE patients were significantly lower than in the G1 control group (P< 0.001). When compared to the control group, G1, the two SLE patient groups (G2 & G3) had noticeably higher ESRs (P < 0.01). The study employed many immunological markers, such as C-reactive protein (CRP), antinuclear antibody (ANA), Anti-double stranded DNA (Anti-dsDNA), complement components C3 and C4 levels. Serum CRP levels were significantly higher in G2 and G3 SLE patients (P<0.001) than in the G1 control group. Research revealed that two SLE patient groups (G2 & G3) had blood levels of ANA and Anti-double stranded DNA (Anti-dsDNA) that were considerably higher than those of the control group (G1).